Prioritas Alokasi Sumber Daya Fisik Di Daya Tarik Wisata Danau Paisupok, Banggai Kepulauan, Sulawesi Tengah (Jurnal Destinasi Pariwisata, 2025)
This study aims to determine the priority of physical resource allocation at the Paisupok Lake Tourist Attraction, Banggai Kepulauan, Central Sulawesi. A quantitative approach was applied using the Analytical Hierarchy Process (AHP), supported by Expert Choice software. A total of 15 respondents comprising heads and staff of the Banggai Kepulauan Tourism Office were selected through purposive sampling based on specific criteria, including experience, capacity, and contextual understanding of tourism resource management. The findings reveal that Infrastructure holds the highest priority with a weight of 0.4601, followed by Sustainable Facilities (0.3859), Location Map (0.0851), and Legal Basis/Policy (0.0689). Infrastructure, such as road access, plays a critical role in improving accessibility, safety, and destination competitiveness. The use of AHP proved effective in identifying and prioritizing strategic needs based on measurable criteria. This research has important implications for evidence-based decision-making, tourism planning, and efficient resource allocation. AHP provides a clear framework for both short- and long-term development plans, ensuring resources budget, labor, time are allocated to the most impactful areas. Long-term, the findings support the environmental, social, and economic sustainability of Paisupok Lake. Furthermore, this method can be replicated in other tourist destinations with similar characteristics, contributing to more integrated and participatory tourism management policies at the regional level.